2006
DOI: 10.1590/s0100-69912006000100008
|View full text |Cite
|
Sign up to set email alerts
|

Janela pericárdica transdiafragmática no diagnóstico de lesão cardíaca

Abstract: OBJETIVO: Avaliar a eficácia e as complicações da utilização da janela pericárdica (JP) transdiafragmática no diagnóstico de lesão cardíaca por ferimento penetrante. MÉTODO: No período de janeiro de 1994 a dezembro de 2004 a JP foi indicada em 245 casos com suspeita de trauma cardíaco por ferimento penetrante. Em 38 deles (15,5%) a JP foi realizada através de acesso transdiafragmático, constituindo a população do presente estudo. RESULTADOS: O mecanismo de lesão foi ferimento por projétil de arma de fogo (FPAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This study identified a non-significant prevalence of injuries in the left ventricle, amounting to eight cases (47.1%), followed by the right ventricle in six cases It presents 100% sensitivity and 96.9% specificity 13 .…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…This study identified a non-significant prevalence of injuries in the left ventricle, amounting to eight cases (47.1%), followed by the right ventricle in six cases It presents 100% sensitivity and 96.9% specificity 13 .…”
Section: Discussionmentioning
confidence: 87%
“…The right ventricle is often described as the most affected cardiac chamber in penetrating injuries, because it accounts for most of the anterior surface of the heart (sternocostal), with predominance ranging from 30% to 48% 3,8,13,[19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations